Lived Experiences of Parents with Prolonged Grief Disorder After Losing Their Child in Accidental Death (Journal of Asian Development Studies, 2025)
The qualitative research explored the lived experiences of parents with prolonged grief disorder who lost their child in an accidental death. This study helps us to understand the intense suffering experienced by parents following the death of a child in an accident, particularly in Pakistani society, where grief is commonly kept a secret. It demonstrates why parents who experience chronic grief require greater understanding and care. Through the purposive sampling technique, a sample of 5 participants was selected from hospitals in Rawalpindi and Islamabad. Participants were selected from two hospital settings: three from NIRM Hospital and two from Benazir Bhutto Hospital. Of these, three had been previously diagnosed by clinical psychologists, while the remaining two were assessed and diagnosed during my internship under the supervision of a clinical psychologist. Semi-structured, face-to-face in depth interviews were conducted with research participants. The data were analyzed using interpretative phenomenological approaches. Four major superordinate themes were developed: Psychological and emotional distress, disturbed daily life functioning, spiritual challenges, and help-seeking behaviour. The results of this study can be utilized by mental health practitioners, grief counsellors, and legislators to develop more effective and better support systems for parents experiencing prolonged grief disorder.